Overview of alternative ethanol removal techniques for enhancing bioethanol recovery from fermentation broth - Zentou, Hamid; Zainal Abidin, Zurina; Yunus, Robiah; Awang Biak, Dayang Radiah; Korelskiy, Danil (MDPI, 2019)
This study aims at reviewing the alternative techniques for bioethanol recovery, highlighting its advantages and disadvantages, and to investigate the technical challenges facing these alternatives to be widely used. The findings showed that the integration of these techniques with the fermentation process did not meet a large acceptance in the industrial sector. The majority of conducted studies were mainly focusing on ethanol recovery from aqueous standard solution rather than the investigation of these techniques performance in fermentation-separation coupled system. In this context, pervaporation has received more attention as a promising alternative to distillation. However, some challenges are facing the integration of these techniques in the industrial scale as the fouling problem in pervaporation, the toxicity of solvent in liquid extraction, energy consumption in vacuum fermentation. It was also found that there is a lack of the technical economic analysis for these techniques which may limit the spread of its application in the large scale. Currently, hybrid systems integrating distillation with other alternative techniques are considered as an innovative solution to reduce the high cost of the distillation process and the low separation efficiency of the alternatives techniques.